PENAMPILAN SISWA PADA SIMPEL PRESENT TENSE MENGGUNAKAN ULAR TANGGA PADA SISWA KELAS VIII MTA MAMBAUL ULUM KUBU PADI - Maryunah, Maryunah; Nizarrahmadi, Nizarrahmadi (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
The purpose of this study was to improve student’ ability in learning English by using the snake and ladder game method. This research was conducted through Classroom Action Research (CAR). The subject of this study were a group of 16 students of class VII A MTs Mambaul Ulum in the 2021/2022 academic years. The purpose of this study was to determine the improvement of students’ ability in class in using the game of snake and ladder in simple present tense English Grammar. This research was conducted in three test consist of planning, acting, observing, and reflecting. Data were collected using quantitative data. The result of this study indicate that there is an increase in students’ ability to learn English by using the snake and ladder game method. The mean value of the Initial pre-test was 57.91. The average value of the Cycle 1 pre-test was 68.75, while the Cycle 2 post-test average was 77.29. The percentage of students on the result of the Initial pre-test who scored 70 or more was 3 students. The percentage of students on the result of the Cycle 1 pre-test who scored 70 or more was 8 students. Meanwhile, the percentage of students on the Cycle 2 post-test result who scored 70 or above was 1 students. In other word, students’ ability to master grammar is very good at the first meeting until the next meeting.